The Impact of an Educational Support Program on Formal Caregivers of Elderly People with Dementia in the Institutional Context - Miranda, Alexandra; Dias, Maria Isabel; Lopes Gunes, Alexandra Cristina (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
With the aging of the population and the increase of social services tackling their needs, it has been increasing the concern about the qualifications of formal caregivers, with the aim of continuous improvement of the quality of the services they provide to the elderly. The goal of this study is to evaluate the impact of an educational support program on formal caregivers of elderly people with dementia in an institutional context. It follows a quasi-experimental design where the 97 formal caregivers that have participated in the study came from two different institutions. They were randomly selected to participate in an educational support program on dementia, with two groups formed: a control group and an experimental group. Pre and post-training tests were used to evaluate knowledge and perceptions about dementia in old age. Findings suggest that the impact of the educational support program has improved knowledge and perceptions about dementia in old age among formal caregivers.